2019
DOI: 10.5089/9781498320863.001
|View full text |Cite
|
Sign up to set email alerts
|

Income Inequality and Government Transfers in Mexico

Abstract: We analyze microdata from Mexico's survey on household income and expenditures (ENIGH) to study the evolution of income inequality in Mexico over 2004-16, identify its sources, and investigate how it was affected by government social policy. We find evidence of only a small decline in inequality over this period. The observed decline may be attributed to government transfers, notably targeted cash transfers (Prospera) and non-contributory pensions. In 2016, those two programs accounted for more than two third… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…The lowest FGTI level for self-employed workers is observed in Nuevo Le on for women and Baja California for men, with an FGTI value of 0.0089 and 0.0052, respectively; the percentage variation from the national total was -53.8% for women and -87.0% for men. As in the inequality analysis, the statistics for the north of Mexico presented the lowest levels of poverty than those for the south, a result also presented in similar studies (Lambert and Park, 2019).…”
Section: Fgti Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The lowest FGTI level for self-employed workers is observed in Nuevo Le on for women and Baja California for men, with an FGTI value of 0.0089 and 0.0052, respectively; the percentage variation from the national total was -53.8% for women and -87.0% for men. As in the inequality analysis, the statistics for the north of Mexico presented the lowest levels of poverty than those for the south, a result also presented in similar studies (Lambert and Park, 2019).…”
Section: Fgti Resultssupporting
confidence: 75%
“…The case of Mexico is relevant for the literature that analyzes the relationship between poverty and inequality because the implementation of public policies have not had the expected effect on reducing poverty and income inequality (García et al, 2012;Sastr e and Rey, 2008;Sz ekely et al, 2007). Recent empirical evidence points out that the majority of programs based on transfers have not been effective in fulfilling their objectives (Lambert and Park, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…With respect to the study’s limitations, the data on financial help is self-reported by older adults and it may suffer from recall bias. In addition, it is possible that the elderly population under-reported their income ( 17 ), which could bias the results and conclusions of the study. Nevertheless, the study’s principal strength relies on the comparison of two cohorts 11 years apart, and the insights gained allow a better understanding of the changes in economic help from children to their older parents over a decade of rapid population aging and enactment of important social programs in Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…Populist measures do not result in long‐term solutions as increasingly demanded by poorer segments of Latin American population. Policy‐makers have to offer “exit” solutions and strategies for people enrolled in these income transfer programs (Lambert & Park, 2019; Silva & Paes, 2019).…”
Section: Challenges and Opportunities: “Sticking Issues”mentioning
confidence: 99%
“…Altogether, these factors tend to deeply affect the region's ability to weather domestic and global economic downswings. Moreover, it also affects the region's ability to implement sustainable development and growth strategies (Cabral, 2020; Lambert & Park, 2019; Pienknagura, Roldos, & Werner, 2020; Reeves, 2020; Statista, 2020).…”
Section: Introductionmentioning
confidence: 99%